2020
DOI: 10.5863/1551-6776-25.4.278
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Clonidine Transition Protocol on Dexmedetomidine Withdrawal in Critically Ill Pediatric Patients

Abstract: OBJECTIVES This study describes our experience with a clonidine transition protocol to prevent dexmedetomidine (DEX) withdrawal in critically ill pediatric patients. METHODS Retrospective review of electronic medical records of patients in the pediatric intensive care unit of a single tertiary children's hospital. All patients up to 19 years of age, who received concomitant DEX infusion and enteral clonidine between June 1, 2016, and May 31, 2018, were included. RESULTS Two of 24 encounters had DEX restarted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…11,12,20 It has been suggested that Dex's prolonged infusions may be associated with rebound tachycardia, hypertension, and withdrawal symptoms with rapid discontinuation. 21 There was no report of rebound hypertension in this cohort, but due to these possible withdrawal and rebound symptoms, a slow wean approach should be considered for a patient on long term Dex therapy (more than 5 days). In this study, 9 (9%) of the infants received Clonidine because they did not tolerate a rapid wean of the drip.…”
Section: Discussionmentioning
confidence: 77%
“…11,12,20 It has been suggested that Dex's prolonged infusions may be associated with rebound tachycardia, hypertension, and withdrawal symptoms with rapid discontinuation. 21 There was no report of rebound hypertension in this cohort, but due to these possible withdrawal and rebound symptoms, a slow wean approach should be considered for a patient on long term Dex therapy (more than 5 days). In this study, 9 (9%) of the infants received Clonidine because they did not tolerate a rapid wean of the drip.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have relied on the Withdrawal Assessment Tool (WAT-1), a scoring system developed and validated to monitor for the development of iatrogenic opioid and benzodiazepine withdrawal, to identify the development of central α 2 -adrenergic agonist withdrawal. 10,[12][13][14]17,18,21 The WAT-1 is a 12-point scale scoring system, which includes tremor and agitation in its criteria, but the tool is not Clonidine for Prolonged Dexmedetomdine in Critically Ill Children Crabtree et al…”
Section: Discussionmentioning
confidence: 99%
“…To the knowledge of the study team, there is only one pediatric study outside of this institution that has described an enteral clonidine dosing strategy to prevent dexmedetomidine withdrawal. 18 Liu et al found that five patients (35.7%) who received an initial enteral clonidine dose of 2 µg/kg/dose every 6 hours (8 µg/kg/day) required a clonidine dose increase compared with one patient (10%) in the group of patients who received an initial dose of 4 µg/kg/dose every 6 hours (16 µg/kg/day). 18 However, the study by Liu et al along with other previous studies have not excluded patients with exposure to other continuous infusion sedative agents, and thus can influence findings as it relates specifically to dexmedetomidine exposure and withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations